2020
DOI: 10.1038/s41598-020-71244-y
|View full text |Cite
|
Sign up to set email alerts
|

In-plane anisotropic third-harmonic generation from germanium arsenide thin flakes

Abstract: A newly introduced two-dimensional (2D) layered germanium arsenide (GeAs) has attracted growing interest due to its promising highly in-plane anisotropic crystal structure and electronic properties for photonic and optoelectronic applications. The potential of 2D layered GeAs for many applications such as anisotropic photodetection, electronics, superconductivity and thermoelectricity is being investigated in recent studies. However, the intrinsic nonlinear optical properties of 2D layered GeAs have not been e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…On the other hand, under the perpendicular configuration the Raman intensity patterns show the anisotropic four-lobe patterns with the maximum and the second maximum intensities located around either 45° and 225° or 135° and 315°. Moreover, the angle-resolved Raman mode analysis can be used to identify the crystal axis 24 , 41 43 . Based on the current observations, it is confirmed that x -axis (0°) and y -axis (90°) are identified as the rippling direction (along the b -axis) and its perpendicular direction (along the a -axis), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, under the perpendicular configuration the Raman intensity patterns show the anisotropic four-lobe patterns with the maximum and the second maximum intensities located around either 45° and 225° or 135° and 315°. Moreover, the angle-resolved Raman mode analysis can be used to identify the crystal axis 24 , 41 43 . Based on the current observations, it is confirmed that x -axis (0°) and y -axis (90°) are identified as the rippling direction (along the b -axis) and its perpendicular direction (along the a -axis), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Thereby, only four non‐zero elements χ11, χ18, χ22, and χ29 will contribute to the in‐plane THG emission process. The electric field components of THG emission and the THG intensity can then be written as: [ 40 ] E()3ω=Ex()3ωEy()3ωEz()3ωε0E3χ11cos3θ+3χ18cosθsin2θχ22sin3θ+3χ29sinθcos2θ0 Ix()3ω()χ11cos3θ+3χ18cosθsin2θ2 Iy()3ω()χ22sin3θ+3χ29sinθcos2θ2…”
Section: Resultsmentioning
confidence: 99%
“…[38] Here, the 0°and 90°directions are identified as the a-axis and b-axis of getchellite crystal, [39] for further probing the anisotropic linear and nonlinear optical responses of the crystal. [38][39][40]…”
Section: Raman Spectroscopy Characterization Of Getchellite Crystalmentioning
confidence: 99%
“…The lattice orientation of the anisotropic crystal system of nagyágite can be determined through angle‐resolved polarized Raman spectroscopy. Previously, this technique has been used for other monoclinic crystal systems such as GeAs [ 31 ] and MoTe 2 . [ 32 ] Figure 3b,c are contour color maps of the Raman intensity variation of the parallel and perpendicular polarization components as a function of the incident polarization angle (θ) with respect to the x ‐axis (θ = 0°).…”
Section: Resultsmentioning
confidence: 99%